Color stability of ceramic laminate veneers cemented with light-polymerizing and dual-polymerizing luting agent: A split-mouth randomized clinical trial - Marchionatti, Ana Maria Estivalete; Wandscher, Vinícius Felipe; May, Michele Mirian; Bottino, Marco Antonio [UNESP]; May, Liliana Gressler (Elsevier, 2017)
Statement of problem The color stability of luting agents influences the esthetics of ceramic laminate veneers. Clinical studies that have evaluated the color changes of veneers cemented to enamel with light- and dual-polymerizing resin cement are lacking. Purpose The purpose of this split-mouth randomized clinical trial was to evaluate the color change and marginal discoloration of dual- and light-polymerizing cement used for cementation of ceramic laminate veneers. Material and methods In 10 participants, 0.3-mm-thick ceramic laminate veneers were cemented on the buccal surface of the second premolars without tooth preparation. A randomized application of light-polymerized cement was used on one side and a dual-polymerized cement on the contralateral side. The operator and participants were blinded to the activation mode. Color was evaluated by a blinded evaluator with a spectrophotometer at 24 hours and at 2, 6, 12, and 24 months after cementation. The CIELab (ΔE*ab) and CIEDE2000 (ΔE*00) formulas were used to quantify color alteration, and Δa* Δb* and ΔL* were calculated between the first and subsequent measurements. US Public Health Service guidelines were used to evaluate the marginal discoloration. Results Wilcoxon tests did not show a statistical difference in ΔE*ab and ΔE*00 between the groups (P>.05). At 24 months, the median ΔE*ab was 2.31 (interquartile ranges [IQR]: 3.34) for the light-polymerizing mode and 1.57 (IQR: 0.41) for the dual-polymerizing mode, while the median ΔE*00 was 1.65 for the light-polymerizing mode (IQR: 2.34) and 1.18 for the dual-polymerizing mode (IQR: 0.25). The thresholds for clinically acceptable color changes ΔE*ab>3.46 and ΔE*00>2.25 were found for both curing modes. Marginal discoloration was observed from the 2-year assessment. Conclusions The color stability of ceramic laminate veneers was similar for both of the polymerizing modes for all evaluated periods. Marginal discoloration increased over a 2-year period for both the light- and the dual-polymerizing modes.